Morphological, molecular and phylogenetic analyses of the spirurid nematode Stegophorus macronectes (Johnston & Mawson, 1942). Issue 2 (14th April 2015) - Vidal, V.; Ortiz, J.; Diaz, J.I.; Zafrilla, B.; Bonete, M.J.; Ruiz De Ybañez, M.R.; Palacios, M.J.; Benzal, J.; Valera, F.; De La Cruz, C.; Motas, M.; Bautista, V.; et al.
Abstract: Stegophorus macronectes (Johnston & Mawson, 1942 ) is a gastrointestinal parasite found in Antarctic seabirds. The original description of the species, which was based only on females, is poor and fragmented with some unclear diagnostic characters. This study provides new morphometric and molecular data on this previously poorly described parasite. Nuclear rDNA sequences (18S, 5.8S, 28S and internal transcribed spacer (ITS) regions) were isolated from S. macronectes specimens collected from the chinstrap penguin Pygoscelis antarctica Forster on Deception Island, Antarctica. Using 18S rDNA sequences, phylogenetic analyses (maximum likelihood, maximum parsimony and Bayesian inference) of the order Spirurida were performed to determine the phylogenetic location of this species. Primer pairs of the ITS regions were designed for genus-level identification of specimens, regardless of their cycle, as an alternative to coprological methods. The utility of this molecular method for identification of morphologically altered specimens is also discussed.